Marine Safety: Case Study on Safety Equipment Fulfillment towards Ship Safety (Research, Society and Development, 2019)
This study aimed to identify the fulfillment of safety equipment and its effect towards ship safety. This study was conducted at some harbors in Indonesia such as Soekarno Hatta Harbor at Makassar, Tanjung Perak Harbor at Surabaya and Tanjung Priok harbor at Jakarta. The sampling technique was Purposive sampling. Data were collected by questioners with Likert model scale. The obtained data then was being analysed using descriptive statistic and inferential statistic consisted of regression analysis and correlation. The result showed that there were positive and significant effects between safety equipment fulfilment and sailor ship safety. The regression equation was. Moreover, safety equipment fulfilment had strong effects toward sailor ship safety with 0.753 coefficient correlation 55.3% contribution. Further, the other 44.7% was influenced by other variables.